Astringency in ‘Giombo’ persimmon and its relationship with the harvest time - Tessmer, Magda Andréia; Appezzato-da-Glória, Beatriz; Kluge, Ricardo Alfredo (Revista Ceres, 2016)
‘Giombo’ is one of most cultivated persimmon cultivars in Brazil. It is a late-harvest cultivar and requires treatment for astringency removal. The aim of this study was to evaluate the efficiency of ethanol and the effect of harvest time on reducing astringency, physicochemical and anatomical characteristics of ‘Giombo’ persimmon. Two experiments were carried out, one in each growing season, with five treatments corresponding to exposure to 1.70 mL kg-1ethanol for 0, 12, 24, 36 and 48 hours. At the end of the growing season (2011) the fruits achieved the astringency index and levels of soluble tannins suitable for consumption in 24 hours, and at the beginning of the growing season (2012) in 36 hours, indicating that the efficiency of the treatment is related to harvest time and ethanol exposure time. Astringency removal with ethanol affects the cell structure with accumulation of substances inside the cells and in intercellular spaces, resulting in the degradation of the parenchyma cell wall. To avoid such damage and maintain fruit quality, it is recommended the combination of low ethanol doses with less ethanol exposure time.